Comparative effects of flywheel and traditional resistance training on reactive strength and multidirectional COD in elite badminton players - Tan, Shiwen; Lu, Zepeng; Yuan, Shurui; Zhang, Zijie; Zou, Yixuan; Zhang, Meiyi; Zhang, Litian; Li, Shuairan; Dai, Jin (Frontiers in Physiology, 2025)
PurposeThis study compared the effects of flywheel resistance training (FRT) versus traditional resistance training (TRT) on reactive strength, dynamic balance, and sport-specific change-of-direction (COD) ability in elite badminton players.MethodsTwenty-four athletes (mean age: 21.2 ± 2.2 years) were randomly allocated to an FRT group (n = 12) or a TRT group (n = 12). Over 6 weeks, both groups performed twice-weekly sessions of squats, deadlifts, and lunges at a rating of perceived exertion ≈8. Performance was assessed before and after the intervention using the SEMO agility test, modified 5–10-5 COD test, 10-m sprint, reactive strength index (RSI), and Y-Balance test. Data were analyzed with a two-way mixed ANOVA (p < 0.05).ResultsMixed ANOVA revealed significant main effects of time for the SEMO test, modified 5–10-5 COD test, and 10-m sprint (all p < 0.001, η2 = 0.56–0.79), indicating performance improvements at post-test in both training groups. No significant group × time interactions were observed for these variables (p = 0.07–0.23). Within-group effect sizes for these speed and COD measures were large in the FRT group (SEMO: Cohen’s d = 1.01; 5–10-5: d = 1.21; 10-m sprint: d = 1.27) and ranged from small to large in the TRT group (d = 0.40–0.87). For RSI, both the main effect of time and the group × time interaction were significant (p < 0.001, η2 = 0.90 and 0.66, respectively). Within-group effect sizes were large in the FRT group (d = 2.43) and moderate in the TRT group (d = 0.79). Y-Balance Test improved over time for both dominant and non-dominant limbs (p < 0.001, η2 = 0.53–0.57), with no significant group × time interaction (p > 0.75).ConclusionThese findings suggest that FRT may provide additional advantages over TRT in enhancing reactive strength and COD ability, likely due to eccentric overload-induced neuromuscular adaptations. However, both training modalities were similarly effective in improving dynamic balance. These findings have practical implications for coaches: incorporating twice-weekly FRT into badminton-specific conditioning may optimize deceleration mechanics and multidirectional COD and improve transfer of strength gains to on-court performance.